2017
DOI: 10.1038/ncomms15879
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic rewiring of thalamocortical circuits to restore function in the stroke injured brain

Abstract: To regain sensorimotor functions after stroke, surviving neural circuits must reorganize and form new connections. Although the thalamus is critical for processing and relaying sensory information to the cortex, little is known about how stroke affects the structure and function of these connections, or whether a therapeutic approach targeting these circuits can improve recovery. Here we reveal with in vivo calcium imaging that stroke in somatosensory cortex dampens the excitability of surviving thalamocortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 68 publications
8
100
0
Order By: Relevance
“…We first evaluated the effect of four weeks of repeated stimulation of the ipsilesional cortex. In agreement with a previous work by Tennant and collaborators (Tennant et al, 2017) showing that optogenetic stimulation of thalamocortical axons over the entire dorsal cortex enhances the recovery of forepaw sensorimotor abilities, we found that four weeks of optogenetic stimulation targeted to ChR2-transfected perilesional cortex leads to a remarkable motor improvement. Nevertheless, our observations indicate that this treatment per se does not recover pre-stroke features of motor-evoked cortical activation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We first evaluated the effect of four weeks of repeated stimulation of the ipsilesional cortex. In agreement with a previous work by Tennant and collaborators (Tennant et al, 2017) showing that optogenetic stimulation of thalamocortical axons over the entire dorsal cortex enhances the recovery of forepaw sensorimotor abilities, we found that four weeks of optogenetic stimulation targeted to ChR2-transfected perilesional cortex leads to a remarkable motor improvement. Nevertheless, our observations indicate that this treatment per se does not recover pre-stroke features of motor-evoked cortical activation.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that repeated optogenetic neuronal stimulation of the ipsilesional hemisphere induces a significant improvement in neurovascular coupling response (Cheng et al, 2014). Furthermore, it has been demonstrated that chronic optogenetic stimulation of the entire cortical mantle promotes behavioral recovery associated with the formation of new and stable thalamocortical synaptic boutons (Tennant et al, 2017). Even though large-scale remapping is known to be an important factor in the recovery of lost functionalities (Siegel et al, 2016;Siegel et al, 2018), how the global activity over the ipsilesional hemisphere is redistributed after optogenetic stimulation is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical stimulation of thalamocortical axons at 10 Hz augments motor cortical activity (Castro‐Alamancos, ; Miall et al, ). ChR2 stimulation of thalamocortical axons at 5 or 10 Hz enhances the recovery of somatosensory cortical circuit function and forepaw sensorimotor abilities after stroke (Tennant, Taylor, White, & Brown, ). In our experimental condition, 10 Hz stimulation of thalamocortical axons reliably induced the cortical response in WT mice (the average number of M1 unit responses to the stimulation was 1.93 ± 0.08, n = 31 units from two mice).…”
Section: Resultsmentioning
confidence: 99%
“…ChR2 stimulation of thalamocortical axons at 5 or 10 Hz enhances the recovery of somatosensory cortical circuit function and forepaw sensorimotor abilities after stroke (Tennant, Taylor, White, & Brown, 2017). In our experimental condition, 10 Hz stimulation of thalamocortical axons reliably induced the cortical response in WT The spontaneous firing rates of L2/3 (left) and L5 (right) neurons during the awake state (L2/3: p = 2.3 × 10 −10 , n = 68 units from 10 WT mice, n = 56 units from 13 PLP-tg mice; L5: p = .049, n = 55 units from nine WT mice, n = 58 units from nine PLP-tg mice, Wilcoxon rank sum test).…”
Section: Synchronous Stimulation Of Thalamic Afferents Rescues Thementioning
confidence: 99%
“…Our data reveal that particularly M2-DLS pathway is profoundly compromised in our R6/1 mouse model of HD. The idea to treat brain circuits using optogenetic tools is object to study in many neurological disorders, such as Parkinson (Gradinaru et al, 2009;Kravitz et al, 2010;Magno et al, 2019), stroke (Cheng et al, 2014;Tennant et al, 2017) and psychiatric disorders (Fuchikami et al, 2015). In this line, we aimed to restore circuit function in HD by increasing selected cortico-striatal activity in symptomatic mouse.…”
Section: Discussionmentioning
confidence: 99%